Culture-Related Issues in Teacher Education Programs: The Last Decade in Colombia - Alexánder Ramírez-Espinosa (Asociación Colombiana de Profesores de Ingles, 2023)
This paper showcases a literature review in 13 Colombian refereed journals, covering the last decade, from 2011 to 2021. Data were collected from the virtual platforms where each journal hosts published issues. A thematic analysis was conducted with the sample of papers. The purpose of the review was twofold. On the one hand, it aimed at establishing the main research concerns of Colombian scholars regarding the place of culture in the context of Foreign Language Teacher Education programs. On the other hand, the review aimed at exploring the implications for curriculum design in Colombia that can be drawn from culture-related literature produced by scholars in the last decade. Results suggest that the treatment of culture-related issues in Foreign Language Teacher Education programs has gained currency, although scholarship in the last decade has mainly focused on a diagnostic stage.